2015 IEEE International Conference on Big Data (Big Data) 2015
DOI: 10.1109/bigdata.2015.7363860
|View full text |Cite
|
Sign up to set email alerts
|

Towards real-time customer experience prediction for telecommunication operators

Abstract: Telecommunications operators (telcos) traditional sources of income, voice and SMS, are shrinking due to customers using over-the-top (OTT) applications such as WhatsApp or Viber. In this challenging environment it is critical for telcos to maintain or grow their market share, by providing users with as good an experience as possible on their network. But the task of extracting customer insights from the vast amounts of data collected by telcos is growing in complexity and scale everey day. How can we measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…In [18] study the quality of service is highly significant in tandem with, customer satisfaction, possession of superior technology, and cost of change and advertising. Difference between this findings and other like [16] [5] [16] [21] [20] on logistic regression may be attributable to the rigor on data selection and cleaning as well as the number of classification employed. The study of [23] that adopted the use of data mining tools to select and classify features within the selected customer churn dataset pointed out that Logistic Model is the best method due to its accuracy using neutral network, while this however, do not reflect the outcome of this study and differs from [32] that study showed that the different data mining techniques improve the prediction accuracy of the models because of the combined advantages of the components.…”
Section: Ivdiscussion Of Findingscontrasting
confidence: 71%
“…In [18] study the quality of service is highly significant in tandem with, customer satisfaction, possession of superior technology, and cost of change and advertising. Difference between this findings and other like [16] [5] [16] [21] [20] on logistic regression may be attributable to the rigor on data selection and cleaning as well as the number of classification employed. The study of [23] that adopted the use of data mining tools to select and classify features within the selected customer churn dataset pointed out that Logistic Model is the best method due to its accuracy using neutral network, while this however, do not reflect the outcome of this study and differs from [32] that study showed that the different data mining techniques improve the prediction accuracy of the models because of the combined advantages of the components.…”
Section: Ivdiscussion Of Findingscontrasting
confidence: 71%
“…end-to-end, which means that not even WhatsApp can read our messages [12,16,35]. Following WhatsApp's move to adding end-to-end encryption to its platform, on April 19, 2016 Viber implemented end-to-end encryption for all messages and [3,12,18], while Telegram uses a symmetrical encryption scheme called MTProto. The protocol was developed by Nikolai Durov and is based on 256-bit symmetric AES encryption, RSA 2048 encryption and Diffie-Hellman key exchange.…”
Section: End-to-end Encryptionmentioning
confidence: 99%
“…Viber also offers two modes of voice quality: the normal and HD modes, with the latter very beneficial on high bandwidth networks. Perhaps the most unique feature is the Viber Out, which make it possible to Viber users to be in contact with people who are not on the service [3,17,18]. …”
Section: Vibermentioning
confidence: 99%